FEATURES OF IMMUNE REACTIONS IN STRESS CONDITIONS ASSOCIATED ASSOCIATED WITH EXAMS - I. V. Shirolapov (SPb RAACI, 2014)
Abstract. It has been widely accepted that routine psychophysiological stressors may influence immune functioning via their close interactions between nervous, autonomic, endocrine and immune regulatory systems. The aim of this study was to evaluate immune reactions to acute psychophysiological stress in 203 medical students before and after academic exams. The results showed significant decrease of absolute and relative contents CD3+ T cells, natural killer (NK) cell subpopulations and T-NK cells (CD3-CD16+CD56+ and CD3+CD16+CD56+), as well as declined NK cell activity were revealed immediately after exams, as compared to initial values for these indices. Moreover, a significant decrease in CD19+ B cells, CD4+ T-helpers and CD8+ T-cytotoxic lymphocyte counts was found after exams, in comparison with parameters assessed under stress-free conditions, but no differences were observed, when compared with pre-examination values. Serum concentrations of IgA, IgM, IgG were within normal physiological limits. Changes in immunological parameters during acute examination-associated stress depend on characteristics of autonomous and hormonal reactions in humans, and, under particular extreme conditions, such psycho-emotional stress may cause general disturbances of immune reactions. We conclude that acute psycho-physiological stress during the exams causes significant changes in some lymphocyte subpopulations, in particular, natural killers.